(untitled) (Research, Society and Development, 2025)
Guillain-Barré Syndrome (GBS) is an acute inflammatory demyelinating polyradiculoneuropathy characterized by progressive, ascending, and symmetrical flaccid paralysis. It is generally considered a benign condition, as only a small proportion of cases progress to death, most commonly due to acute respiratory failure. GBS is an autoimmune disorder typically preceded by a respiratory or gastrointestinal infection within the previous six weeks, triggering immune-mediated damage to the myelin sheath by activated macrophages. The aim of the present study was to report the case of a child presenting with two clinically compatible episodes suggestive of recurrent Guillain–Barré syndrome. Neurological examination revealed ataxia, with muscle strength graded 2/5 in the lower limbs and 4/5 in the upper limbs. The patient had a prior history of hospitalization at the age of three for thirteen days at a pediatric referral center due to Guillain-Barré syndrome. During the current hospitalization, cerebrospinal fluid analysis demonstrated elevated protein levels, and nerve conduction studies revealed a demyelinating polyneuropathy consistent with Guillain-Barré syndrome. Treatment with intravenous immunoglobulin at a dose of 0.4 g/kg/day for five consecutive days was initiated, with follow-up by the pediatric neurology team, resulting in progressive recovery of muscle strength and improvement in ambulation with support. This case emphasizes the importance of considering Guillain-Barré syndrome recurrence in pediatric patients, despite its rarity and the limited number of cases reported in the literature.